Evaluation of serum zinc and copper in children with chronic kidney disease - Youssef, Doaa M.; Noseer, Ateef I.; Abdallah, Ahmed M.; Aboelmagd, Yosry E. (Journal of Pediatric Biochemistry, 2012)
Trace elements may be modified by dialysis procedures. To prevent complications in chronic hemodialysis patients, it is important to understand and regulate the levels of trace elements. The aim of this work is to evaluate the serum zinc (Zn) and copper (Cu) levels in children with chronic kidney disease. This case control study has 3 groups: 20 children with chronic kidney disease (CKD) stage 5 on regular hemodialysis as group A, 20 children with CKD stage 3 and 4 on conservative treatment as group B children, and 10 healthy children as control group C. Measurements of serum copper and zinc were performed by atomic absorption spectrophotometry. We found that serum Zn was (74.4 ± 12.6 μg/dL) in group A, (76.7 ± 13.5 μg/dL) in group B with no significant difference between both groups (p > 0.05) but they are both significantly lower than group C in which serum Zn was (97.7 ± 14.3 μg/dL) (p < 0.05). As regard Cu level it was (89.3 ± 15.1 μg/dL) in group A, (95.6 ± 16.2 μg/dL) in group B, while it was (116.6 ± 13.6 μg/dL) in group C which is significantly higher than in children with CKD (p < 0.05). In studying the correlation between Zn, Cu with other parameters either (demographic or laboratory) in our patients we found a significant negative correlation with urea, creatinine and a positive correlation with serum iron level. Serum Zn and Cu levels are significantly decreased in patients with CKD when compared with healthy children. Hence we recommend supplementation of Zn and Cu for patients on regular hemodialysis specially those with iron deficiency.
Keywords: Zinc; copper; chronic kidney disease; hemodialysis; children